Personality traits (ZKPQ) in patients with fibromyalgia: A case-control study. - Albiol, Silvia; Gomà-i-Freixanet, Montserrat; Valero, Sergi; Vega, Daniel; Muro, Anna (Anales de Psicología / Annals of Psychology, 2014)
This is the first study aimed at determining the relationship between fibromyalgia and the Zuckerman-Kuhlman Personality Questionnaire (ZKPQ), and one of the few that aims at establishing the relationship between this diagnosis and normal personality traits. A sample of female adults diagnosed with fibromyalgia (n = 47) was paired by age and sex with normal-range controls (n = 94). Logistic regression analysis showed that high scores on Neuroticism-Anxiety and low scores on Sociability were the most powerful predictors of being endorsed with a diagnosis of fibromyalgia. It seems that the ZKPQ provides more specific subscales and a control scale which might suggest refinements in the assessment of normal personality in fibromyalgia. It is concluded that physicians and psychologists should work together towards an individualized diagnostic assessment of this medical condition and build a model for a better conceptualization of fibromyalgia.